Sleep difficulty mediates effects of vasomotor symptoms on mood in younger breast cancer survivors. (October 2014) - Vincent, A. J.; Ranasinha, S.; Sayakhot, P.; Mansfield, D.; Teede, H. J.
Abstract Objective Treatment-induced early menopause occurs in > 80% of premenopausal women diagnosed with breast cancer. This study explored the relationship between vasomotor symptoms (VMS), sleep and mood in women aged 40–51 years with non-metastatic breast cancer. Methods Cross-sectional study using validated questionnaires (Greene Climacteric scale and Hospital Anxiety and Depression Scale, HADS). Women (n = 114) were recruited from the community and hospital outpatient clinics. Frequency determination and structural equation modeling (SEMod) were used to examine the relationship between the latent variables: VMS, anxiety, and depression, and the indicator variable: difficulty sleeping. Results Participants' mean age was 47 years and 94% became menopausal after breast cancer diagnosis. Difficulty sleeping was reported by 82% of women with 46% reporting (Likert scale) 'quite a bit/extremely'. Most women reported night sweats (77% of women: 47% reporting 'quite a bit/extremely') and hot flushes (84% of women: 50% reporting 'quite a bit/extremely'). HADS scores indicated clinically relevant depression and anxiety in 98% and 99% of women, respectively. SEMod revealed that VMS contributed to difficulty sleeping (standardized coefficient = 0.54; p < 0.001) and difficulty sleeping mediated the relationship between VMS and anxiety (standardized coefficient = 0.34; p = 0.03). However, difficulty sleeping did not have a significant direct impact on depression (standardized coefficient = −0.03; p = 0.8), although anxiety was a strong predictor of depression (standardized coefficient = 0.83; p = 0.015). Conclusions VMS, sleep and mood disturbance are commonly experienced by younger women with breast cancer. Using SEMod, we demonstrate for the first time that VMS may directly influence sleep in these women. VMS may have an indirect effect on mood, partly mediated by sleep difficulty.